Cost Benefit Analyses of Rabi and Kharif Crops in Kashmir Valley: A Case Study of District Anantnag - Din, Towseef Mohi Ud; Mir, Lateef Ahmad; Bhat, Tariq Ahmad (Growth, 2018)
The present study is an attempt to evaluate the cost benefit analyses of two main crops cultivated in district Anantnag of Kashmir valley. In order to satisfy the objectives of the present study a primary survey was conducted in which information were collected about the production cost, market price, perception of farmers about the cultivation, and other necessary aspects of the rice and mustard crops. The study has revealed that cultivation of rice is comparatively more profitable than the cultivation of mustard. It also shows that the production cost of rice is comparatively higher than that of mustard. The study also indorses that more number of hired labours are required for the cultivation of rice than the mustard on land area of same size. The low supply of this hired labour in other districts is considered an important factor of conversion of land from cultivation of rice in to apple fields. The low supply of the rural labour has occurred due to the structural changes in our economic system as a large group of the rural labour force has adopted non –farm activities to earn their lively hood. The result of Chi-square also shows that there is significant difference between the profitability of Rice and Mustard production.